(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Despite the variety of graph coloring models discussed in published papers of a theoretical nature, the classical model remains one of the most significant and widely applied in practice. The NP-hardness of the coloring problem gives rise to the necessity of using suboptimal methods in a wide range of practical applications. Moreover, the large range of problems solved by classical coloring, as well as the variety of graph families with practical significance in this field aids the evolution and development of new suboptimal algorithms. There exist several relatively simple methods, which are regarded as classical due to their date of creation or scope of practical application. As the implementation of a particular algorithmic solution requires the selection of at least one coloring method, it is essential to formulate criteria for the assessment of the suitability of coloring algorithms.